JEALOUSY, BY ITSELF, DOES NOT CONSTITUTE A BASE MOTIVE (CIPEEX, 2025)
This study examines whether jealousy, taken alone, can ground the qualifying circumstance of a “base motive” in crimes such as homicide, setting criteria to distinguish understandable emotion from legally relevant vileness. It departs from the paper’s core question — whether jealousy by itself qualifies the offence — and recognizes that the intensity and forms of manifestation of this feeling may influence legal classification without entailing automatic qualification. The aim is to provide subsumption parameters and avoid presumptions that detach the analysis from the factual context. Methodologically, it adopts an analytical, interdisciplinary literature review (law, psychology and neuroscience) covering scholarship, scientific articles and case law. The findings indicate that, although jealousy may be present in blameworthy behaviour, it does not, by itself, amount to baseness: the qualifier requires additional, objectively reprehensible circumstances (ignoble ends, cruelty, abjection) that heighten the motive’s censure. It concludes that subsumption must consider the full evidentiary record: mere invocation of jealousy — absent other elements showing lowness — is insufficient to qualify the crime on grounds of baseness.
Keywords: jealousy; base motive; violent emotion; criminal law